SPEECH ACT TRANSFER IN UZBEK AND ENGLISH MEDIA TEXTS: A PRAGMATIC AND DISCOURSE-ORIENTED STUDY - Ugiloy Karimova (International Journal of Literature and Language Studies, 2026)
Speech acts represent one of the main instruments for carrying out communicative functions in the process of linguistic interaction. In media communication, speech acts are deliberately used to inform, persuade, criticize, legitimize, and influence the audience. Nevertheless, transferring speech acts between linguistically and culturally different languages like Uzbek and English is a difficult task for translators and media communicators. This paper will analyze the transfer of speech acts in Uzbek and English media texts through pragmatic and discourse-based approaches. Using speech act theory, pragmatics, and theories of translation, the paper will show how illocutionary force, politeness, implicature, and communicative intention are maintained or modified in the process of translation. By applying qualitative comparative analysis to media texts such as news articles, political interviews, editorials, and public media statements, the paper will define the main patterns of speech act transfer, including direct equivalence, pragmatic adaptation, mitigation, intensification, and contextual modification. The results obtained in this paper will show that successful speech act transfer cannot be achieved at the level of grammar and vocabulary alone. It also involves reconstruction of pragmatic and sociocultural meanings. Finally, the paper will propose a functional-pragmatic approach to speech act transfer in Uzbek-English media translation and emphasize the role of a translator as a mediator of communicative intention and cultural norms.